Bohr compactification of separable locally convex spaces - Sidney A. Morris (Electronic Research Archive)
It is not well-known that for each separable real locally convex space, its Bohr compactification is isomorphic as a topological group to the Bohr compactification of the topological group $ \mathbb{R} $ of all real numbers. This is the case for each separable real Banach space. In this expository research note, we state the results explicitly and provide accessible proofs.